Bangladesh Rural Advancement Committee auditors' report and financial statements for the year ended December 31, 1994 - BRAC (© BRAC, 2016)
This Financial Statement prepared by S. F. Ahmed & Co. Chartered Accountants, 128, New Eskaton Road, Dhaka- 1000, Bangladesh